(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2010)
The marshes are very important areas in iraq , in spite of that ,the geotechnical studies are still very limited . Two locations which have been selected for study in this research ; al fohod and al hammar region . The engineering properties of the soil have been studied and focused on the collapse properties and strength of soil , the tests performed on the soaked soil that the water reflowing away from it during the summer time, we expect these regions to develop in the construction and tourism sides.The results reveal that the soil of the two regions contains high percentage of salts ,although the soil soaked with water along the winter. also, it was found that the soil is soft and it is collapse soil and the degree of collapse ranging from severe to moderate.